2004
DOI: 10.1016/j.neuroimage.2004.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Covariance PET patterns in early Alzheimer's disease and subjects with cognitive impairment but no dementia: utility in group discrimination and correlations with functional performance

Abstract: Although multivariate analytic techniques might identify diagnostic patterns that are not captured by univariate methods, they have rarely been used to study the neural correlates of Alzheimer's disease (AD) or cognitive impairment. Nonquantitative PET scans were acquired during rest in 17 probable AD subjects selected for mild severity [mean-modified Mini Mental Status Examination (mMMS) 46/57; SD 5.1], 16 control subjects (mMMS 54; SD 2.5) and 23 subjects with minimal to mild cognitive impairment but no deme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
98
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 73 publications
6
98
1
2
Order By: Relevance
“…The pattern of reduced blood flow measured in our study was asymmetric, and in agreement with the findings of (Minoshima et al, 1994b;Reiman et al, 1996b;Scarmeas et al, 2004) who used PET 15 O imaging in an AD sample. A variety of PET studies in AD have demonstrated asymmetrically reduced blood flow or metabolic activity in AD patients (Foster et al, 1983;Ishii et al, 2005b;Kawachi et al, 2006;Koss et al, 1985;Martin et al, 1986) and in elderly individuals with cognitive decline (Hunt et al, 2007); however the biological underpinnings of these asymmetries are not quite known.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The pattern of reduced blood flow measured in our study was asymmetric, and in agreement with the findings of (Minoshima et al, 1994b;Reiman et al, 1996b;Scarmeas et al, 2004) who used PET 15 O imaging in an AD sample. A variety of PET studies in AD have demonstrated asymmetrically reduced blood flow or metabolic activity in AD patients (Foster et al, 1983;Ishii et al, 2005b;Kawachi et al, 2006;Koss et al, 1985;Martin et al, 1986) and in elderly individuals with cognitive decline (Hunt et al, 2007); however the biological underpinnings of these asymmetries are not quite known.…”
Section: Discussionsupporting
confidence: 91%
“…Two regions of reduced blood flow were also measured, namely the posterior cingulate and a fairly extended area in the left parietal and parieto-temporal cortex. Most of these regions are known to be affected by AD (Ardekani et al, 2007;Chetelat et al, 2002;Convit et al, 1997;Dickerson et al, 2001;Firbank et al, 2007;Fox and Schott, 2004;Fox et al, 1996b;Frisoni et al, 2007;Ishii et al, 2005a;Jack et al, 1999;Karas et al, 2007;Killiany et al, 2000;Krasuski et al, 1998;Matsuda et al, 2002;Pantano et al, 1999;Pennanen et al, 2005b;Thompson et al, 2007); however, it is their combination via high-dimensional pattern classification that leads to high diagnostic accuracy on an individual basis.The pattern of reduced blood flow measured in our study was asymmetric, and in agreement with the findings of (Minoshima et al, 1994b;Reiman et al, 1996b;Scarmeas et al, 2004) who used PET 15 O imaging in an AD sample. A variety of PET studies in AD have demonstrated asymmetrically reduced blood flow or metabolic activity in AD patients (Foster et al, 1983;Ishii et al, 2005b;Kawachi et al, 2006;Koss et al, 1985;Martin et al, 1986) and in elderly individuals with cognitive decline (Hunt et al, 2007); however the biological underpinnings of these asymmetries are not quite known.…”
supporting
confidence: 91%
“…In general, multivariate analysis might have increased sensitivity compared to univariate analysis even when the disease-related changes in CBF originate in clearly circumscribed foci and spread spatially during the disease course (Scarmeas et al, 2004). Multivariate analysis can detect these subtle, but robust changes, although univariate analysis might experience overly stringent false-positive corrections that tend to 'correct away' the true effects (as evidenced by the results of our voxelwise analysis.)…”
Section: Discussionmentioning
confidence: 85%
“…In this study, we focused our analysis in the GM where most of the dementia-related changes are expected to occur (Scarmeas et al, 2004). Although we did not explicitly measure the transit time difference between the groups, we conjecture that the transit times were not significantly different based on the following: (1) There was no significant difference in CASL CBF values acquired with two different PLDs, indicating that the shorter PLD we chose for this study was optimum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation